THE EFFECTIVENESS OF ZAKAH DISCOURSE AND ITS IMPACT ON THE UNDERSTANDING LEVEL AND THE BUSINESS ZAKAH PAYMENT BEHAVIOUR: A STUDY IN SEPANG, SELANGOR - Siti Umairah Kamaruddin; Hairunnizam Wahid; Mohd Ali Mohd Noor; Abdul Halim Abu Bakar (Journal of Islamic, Social, Economics and Development, 2017)
From a mere glance at zakah collection today, we accomplish that business zakah have the highest potential for the collection of zakah among other zakah on wealth. The recent statistical data of 2016 shows the increasing number of zakah payers from time to time. However, totals collection of zakah funds still lacking according to Selangor Zakah Board (LZS). Considering to this issue, the study intends to examine the quality of zakah discourse by using the gap analysis approach in order to see the difference between the perceptions and expectations of the entrepreneurs. It is then followed by another gap analysis approach to recognize the difference between the perceptions of the entrepreneur who have paid business zakah and entrepreneur who have never paid beforehand with their expectations of zakah discourse. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) and the SERVQUAL model was adopted to investigate whether understanding level, zakat institutions’ role, the allocation of laws and fatwas, the effectiveness of zakah discourse, the physical attractiveness and counseling skills of the motivator and the facilities of programme were the indicator of zakah compliance behaviour based on questionnaire survey of 57 businessmen in one district in Malaysia. The results show that the most commonly influenced of the effectiveness of zakah discourse among entrepreneurs is the role of the understanding level. Recommendations and policy implications are also discussed in the study